Amniotic Membrane Preparation Crucially Affects Its Broad-Spectrum Activity Against Uropathogenic Bacteria - Ramuta, Taja Železnik; Starčič Erjavec, Marjanca; Kreft, Mateja Erdani (Frontiers in Microbiology, 2020)
Urinary tract infections are among the most common bacterial infections in humans. Moreover, they are highly recurrent and increasingly often resistant to antibiotics. The antimicrobial properties of the amniotic membrane (AM), the innermost layer of fetal membranes, have been briefly reported in the literature, however, the results of published studies are often inconsistent and unclear; moreover, its effect on uropathogenic bacteria has not yet been investigated. Further, there is no data in the literature about the effect of AM preparation and storage on its antimicrobial properties. To examine the impact of several preparation procedures on the antimicrobial properties of AM, we prepared patches and homogenates of fresh (fAM) and cryopreserved (cAM) human AM and tested them on 14 selected Gram-positive and Gram-negative uropathogenic bacteria. By employing novel antimicrobial efficiency assays we showed that fAM and cAM homogenates have broad-spectrum antimicrobial activity against all here tested uropathogenic bacteria, except for Serratia marcescens. Moreover, they had a potent effect also on the multiple-resistant clinical strains of uropathogenic Escherichia coli. Interestingly, the patches of fAM and cAM had no antimicrobial effect on any of the tested strains. We therefore prepared and stored AM patches according to the standard procedure for clinical use in ophthalmology, which includes the cryopreservation of antibiotic-treated AM, and performed antimicrobial efficiency assays. Our findings suggest that the ultrastructure of AM patches enables high retention of antibiotics. In addition, we also prepared gentamicin-resistant uropathogenic E. coli strains, which confirmed that the antimicrobial effect of antibiotic-treated AM patches can be attributed to the antibiotic alone. To summarize, here we describe novel protocols for preparation and storage of AM to ensure the preservation of its antimicrobial factors. Moreover, we describe the mechanism of AM retention of antibiotics, based on which the AM could potentially be used as a drug delivery vehicle in future clinically applicable approaches.